A Framework for Universal Energy Inclusion: Definition, Realisation by Social Innovation, and Stakeholder Implementation Guidelines - Hulst, Cornelis (Digital Repository of Theses, 2026)
This thesis addresses the urgent need to reconcile the technical and social dimensions of the global Energy Transition (ET) by introducing a universally applicable definition and benchmarking methodology for Energy Inclusion (EI) and by demonstrating how Social Innovation (SI) can operationalise EI in diverse regional contexts. Three core research questions guide the work. Firstly, how can EI be defined and benchmarked globally across varied socioeconomic settings? Secondly, how can SI principles anchor EI objectives within capital-intensive energy transition development projects (ETDPs)? And thirdly, how can EI targets be planned, implemented and monitored throughout an ETDP lifecycle? Drawing on a three-pillar literature research framework, i.e. Technical Innovation, SI and EI, this study fuses EI theory into a two-factor, nine-level evaluating model and develops a Blueprint non-financial business framework to integrate SI supported by performance indicators. The public–private–community collaboration Blueprint moves beyond Corporate Social Responsibility and embeds EI goals from ET project inception through delivery. Novel contributions are a global EI definition, benchmark tool and SI project implementation guidelines. The framework offers practitioners and policymakers a pathway to inclusive, measurable and social sustainable energy investments.